2016
DOI: 10.1007/s10620-016-4367-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Biliary Leaks and Strictures After Living Donor Liver Transplantation: Optimizing Techniques for Successful Management

Abstract: Endoscopic therapy was successful in almost all patients (98%) and ERCP alone resulted in successful treatment in a higher proportion of patients (93%) than traditionally reported. Advanced endoscopic techniques obviate the need for PTC and/or surgery and allow successful management in almost all LDLT recipients presenting with BC and in patients with recurrence of strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“… 16 Elwir et al reported that ERCP was the only treatment modality in 19 (90%) out of 21 patients who underwent ERCP due to leakage after LDLT. 22 Chok et al reported that half of the patients were successfully treated with endo-radiological method in a very small group of patients (n=12) after LDLT. 23 Although endoscopic treatments have taken priority over surgical treatments in the treatment of biliary stricture, there is still a need for surgical treatments when there is leakage.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Elwir et al reported that ERCP was the only treatment modality in 19 (90%) out of 21 patients who underwent ERCP due to leakage after LDLT. 22 Chok et al reported that half of the patients were successfully treated with endo-radiological method in a very small group of patients (n=12) after LDLT. 23 Although endoscopic treatments have taken priority over surgical treatments in the treatment of biliary stricture, there is still a need for surgical treatments when there is leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating benign from malignant biliary strictures (BBS and MBS respectively) remains a challenge despite advances in imaging and tissue cytogenetic profiling techniques (20)(21)(22). BBS are most commonly iatrogenic in aetiology, and are frequently observed following liver and pancreato-biliary surgery, including cholecystectomy (23)(24)(25). The formation of biliary anastomosis is often complicated by strictures which can be a single, localised (anastomotic strictures) or multiple and rather more proximal to the anastomosis site in their non-anastomotic counterparts (23).…”
Section: Diagnosis and Management Of Benign And Malignant Biliary Stricturesmentioning
confidence: 99%
“…BBSs are more frequent after LDLT than after OLT. [52][53][54][55][56] Overall, the incidence of BBSs is 25%-32% after LDLT [57][58][59][60][61] and 5%-15% after OLT. 39,60,62 The higher incidence of post-LDLT strictures is due to technical aspects of the operation because ductal anastomosis between the donor and the recipient during LDLT is complicated.…”
Section: Post-orthotopic Liver Transplantation Stricturesmentioning
confidence: 99%